GAYA BAHASA PERBANDINGAN PADA NOVEL DANDAMAN KADA BAPANCUNG KARYA ALIMAN SYAHRANI - NORMASUNAH _; Razali Rahman (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
The results of data analysis using stylistic comparisons it was concluded that: (1) The literary style of comparison used in the novel Dandaman Kada Bapancung works Aliman Syahrani is stylistic metaphor, synesthesia, simile, allegory, allusion, hyperbole, kiasmus, personification, sinekdoke, euphemism, perifrasa, and symbolic. (2) The meaning of style in the novel Dandaman comparison Kada Bapancung Aliman work Syahrani is 1. Meaning of synchronous language style (language semantic meaning and cultural significance). 2. Meaning diachronic style. As in the style of metaphorical language in the following sentence of page 3 in the novel Dandaman Kada Bapancung works Aliman Syahrani there are sentences floating nut (flowers of the guava tree) the meaning of the quote in italics above including the meaning of the language style of diachronic because originally said floating nut (flower of the tree guava) is indeed the true sense, but over time, the word is growing and does not always refer to the actual meaning, until finally said floating nut (flowers of the guava tree) growing with new meanings that have meaning gray hair that grows on the head of someone. Keywords: Novel, Language Style Comparison, Meaning